National trends in incidence, mortality, hospitalizations, and expenditures for pemphigus in Taiwan. Issue 3 (September 2020) - Chiu, Hsien-Yi; Chang, Chee Jen; Lin, Yu Jr; Tsai, Tsen-Fang
Highlights: Pemphigus is a fatal blistering disease and causes significant impairments in quality of life of patients. However, there are limited informations on the trends in disease burden of pemphigus in Asian populations. Despite a stable mortality rate, there are recent declines in the medical utilization and expenditure for pemphigus in Taiwan, reflecting better disease control. Nevertheless, we need to investigate strategies to reduce the persistently elevated mortality. Abstract: Background: Data on trends in epidemiological characteristics and economic burden of pemphigus are scarce. Objective: To describe national trends in pemphigus' incidence, mortality, hospitalizations, and expenditures between 2003 and 2015 in Taiwan. Methods: This nationwide study used the Taiwan National Health Insurance Research Database to identify pemphigus patients from 2003 to 2015. Annual incidence, prevalence, healthcare utilization, and expenditure trends were calculated and analyzed. Results: Pemphigus' incidence increased significantly from 3.19 to 4.70 per million person-years in 2003–2010 but fluctuated in 2011−2015. Pemphigus patients had higher mortality and care costs. Medical utilization and expenditure declined for pemphigus inpatients and outpatients. Systemic corticosteroid use decreased, but mortality remained stable. Conclusion: The health expense reduction for pemphigus was mainly attributed to decreased utilization, length of stay, and inpatient costs. The persistently elevated mortality rate highlights an unmet need in pemphigus therapy.